TYPE E BOTULISM IN HOKKAIDO, JAPAN - NAKAMURA, YUTAKA; KARASHIMADA, TAKASHI; SAEKI, KIYOSHI; KANZAWA, KENZO; IIDA, HIROO (Japanese Journal of Medical Science and Biology, 1956)
While considerable work has been done on Clostridium botulinum, both type A and type B, comparatively little is known of the other types, especially of type E. This is due to the infrequency of cases and to the small number of isolated strains of this type. Clostridium botulinum type E was first isolated in Russia from the intestines of a sturgeon and was identified as such in U.S.A. by Ounnison, Cummings and Meyer (1936) . Since then, at least 18 outbreaks of type E botulism have emerged up to 1955 (Dolman and Chang, 1953; Nakamura et al., 1954) . Eight instances occurred in North America: 4 in British Columbia, 2 in New York State, one in California, and one in Alaska. One instance was reported from Russia and from Denmark respectively. In Japan, twelve outbreaks have so far occurred, nine of them taking place in Hokkaido. As pointed out repeatedly by Dolman and his co-workers (1950), one of the most important vehicles of type E botulism is fish. This view is also supported by the fact that all the twelve outbreaks encountered in Japan have proved to have been caused by “Izushi” made of raw fish. The particularly high rate of occurrence in Hokkaido would, therefore, be due to the custom of the inhabitants of eating uncooked fish foodstuffs and also to a possible wide-spread dissemination of type E spores in this province as was detected by the present authors. Strange to relate, in Japan, no cases of botulism have been reported in the literature up to 1952. It is also curious that indigenous spores of Clostridium botulinum have been believed for so many years to be absent from the soil of this country. In previous papers (Nakamura et al., 1952; Nakamura et al., 1954), however, the present authors reported several outbreaks of type E botulism encountered in Hokkaido. They reported at the same time the isolation of several strains of type E organisms, both from the foodstuffs involved and from samples of soil collected in this province. This paper summarizes the epidemiology of the type E botulism observed in Hokkaido and the bacteriological examinations of the type E strains isolated by the present authors.